Synthesis and characterisation of Barium Titanate (BT) dielectric ceramics - Chua, Lin Xiao (2019)
A series of Barium Titanate with an average density of 94.5%, an average shrinkage rate of 13.8% and an average grain size of 0.4 μm to 62.5 μm are successfully produced by two-step sintering method. The effect of the different sintering temperatures on the microstructure of Barium Titanate was studied and subsequently, the effect the microstructure has on the dielectric properties of Barium Titanate. The report found that the sintering temperature 1250°C and below produced fine-grained microstructure and possesses a pseudocubic phase. On the other hand, sintering temperature 1310°C and above produced coarse-grained microstructure and a tetragonal phase. Sintering temperature of 1280°C has shown to produce a microstructure with a mixture of both types of grains and consists of a mixture of cubic and tetragonal phase. A range of dielectric constants from 1500 to 4500 can be obtained from the Barium Titanate samples. The Curie temperature of the Barium Titanate samples are also obtained, showing an increase from 130℃ to 140.5℃ as the sintering temperature increases from 1200℃ to 1400℃. This results show that it is possible to produce Barium Titanate ceramics with excellent dielectric constant and is thus useful to applications on capacitors.